Structural safety assessment and strengthening methods for masonry towers - Paolo Foraboschi (Case Studies in Construction Materials)
This paper focuses on masonry towers, a broad term encompassing various types of tall masonry structures. Their structural analysis remains an underexplored area in the literature, and consequently, is inadequately addressed by codes, standards, and guidelines. Similarly, the topic of strengthening masonry towers has received limited attention.Unlike masonry buildings, where load-carrying capacity is primarily governed by equilibrium – making external loads and their points of application the dominant factors, while masonry compressive strength and maximum acting stresses play a secondary role – the capacity of masonry towers is typically determined by compressive strength. This makes the properties of the masonry material, along with the maximum acting stresses, critical, while kinematic mechanisms play a lesser role. Existing literature and standards, however, predominantly address masonry buildings, neglecting masonry structures where material properties govern load-carrying capacity. This paper aims to bridge these gaps by drawing on the author’s research and professional experience, including the presentation of several case studies. The findings and advancements presented are intended to contribute not only to academic research but also to professional practice.